Analisis Strategi Komunikasi Bisnis pada Warkop Royal Silangkitang Kabupaten Labuhan Batu Selatan - Agus Ardiansyah Ritonga; Ade Khadijatul Z Hrp; Muhlisah Lubis (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This study examines the business communication strategy used by Warkop Royal and the inhibiting factors of Warkop Royal's business communication strategy. To obtain the results of this study, a qualitative descriptive research method was used, then direct interviews were conducted with various sources needed in this study. The results of this study indicate that the communication strategy used by Warkop Royal is to greet consumers with polite language, promote by word of mouth, strategic location, collaboration with local businesses, and maintain the quality of food and beverages. The inhibiting factors of Warkop Royal's business communication strategy are not yet optimal in using social media, lack of training for employees, cultural and language barriers, economic conditions, and tight competition. While the SWOT theory used by Warkop Royal is that they always greet consumers with polite language, Strategy (SO) Using formal but relaxed language. Strategy (WO) Carrying out a more inclusive and adaptive approach. Strategy (ST) Providing polite and friendly language. Strategy (WT) Developing a business approach based on a deep understanding of the local market. When associated with the AIDDA Theory, Warkop Royal's business communication strategy is very promising.